2023
DOI: 10.1039/d2ta09985c
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress on the use of graphene-based nanomaterials in perovskite solar cells

Abstract: Perovskite solar cells (PSCs) are one of the most environmentally renewable technologies for the next generation energy-harvesting devices. The motivation for PSCs as next-generation solar cells stems from their simple...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 271 publications
0
12
0
Order By: Relevance
“…6,22,[32][33][34] LD materials including graphene-related materials (graphene, reduced graphene oxide (rGO), and graphene quantum dots (GQDs)), black phosphorus (BP), and transition metal dichalcogenides such as molybdenum disulfide (MoS 2 ), tungsten disulfide (WS 2 ), and tungsten diselenide (Wse 2 ) have been identified as promising candidates to improve the thermal and chemical stability of PSCs. 6,20,22,[33][34][35][36][37] Incorporating LD materials in different layers of PSCs (e.g., electrode, charge transport layers, or as additives to the absorber layer), works as a good barrier for moisture and oxygen, restrains the migration of ions (from the perovskite into the metal electrode and vice versa), and improves thermal stability. 6,37 As such, LD materials have succeeded in increasing the stability of PSCs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…6,22,[32][33][34] LD materials including graphene-related materials (graphene, reduced graphene oxide (rGO), and graphene quantum dots (GQDs)), black phosphorus (BP), and transition metal dichalcogenides such as molybdenum disulfide (MoS 2 ), tungsten disulfide (WS 2 ), and tungsten diselenide (Wse 2 ) have been identified as promising candidates to improve the thermal and chemical stability of PSCs. 6,20,22,[33][34][35][36][37] Incorporating LD materials in different layers of PSCs (e.g., electrode, charge transport layers, or as additives to the absorber layer), works as a good barrier for moisture and oxygen, restrains the migration of ions (from the perovskite into the metal electrode and vice versa), and improves thermal stability. 6,37 As such, LD materials have succeeded in increasing the stability of PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…6,20,22,[33][34][35][36][37] Incorporating LD materials in different layers of PSCs (e.g., electrode, charge transport layers, or as additives to the absorber layer), works as a good barrier for moisture and oxygen, restrains the migration of ions (from the perovskite into the metal electrode and vice versa), and improves thermal stability. 6,37 As such, LD materials have succeeded in increasing the stability of PSCs. 33,37 LD materials can also enhance the PCE of PSCs with their high carrier mobilities, tunable work function, transparency, and mechanical flexibility.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These materials are also excellent electron transporting materials with high electrical conductivity and thermal stability, which are frequently used in the fabrication of HP-based devices but mainly in the form of an intermediate layer. Such composites are developed for solar cells , and also for photodetectors. ,,,, Most studies reported indeed on MAPbI 3 films or HP islands deposited on a graphene layer, and only few studies have reported on MAPbI 3 mixed with graphene nanocrystals or graphene quantum dots. ,,, All of them reported a charge transfer induced by the presence of graphene. To the best of our knowledge, homogeneous composites constituted of MAPbI 3 and graphite have never been synthesized by mechanosynthesis.…”
Section: Introductionmentioning
confidence: 99%